Last updated at Jan. 17, 2020 by Teachoo
Transcript
Ex 3.3, 10 Express the following matrices as the sum of a symmetric and a skew symmetric matrix: (i) [■8(3&5@1&−1)] Let A = [■8(3&5@1&−1)] A’ = [■8(3&1@5&−1)] 1/2 (A + A’) = 1/2 ([■8(3&5@1&−1)]+ [■8(3&1@5&−1)]) = 1/2 [■8(6&6@6&−2)] = [■8(3&3@3&−1)] 1/2 (A – A’) = 1/2 ([■8(3&5@1&−1)]" − " [■8(3&1@5&−1)]) = 1/2 [■8(0&4@−4&0)] = [■8(0&2@−2&0)] Let, P = 𝟏/𝟐 (A + A’) = [■8(3&3@3&−1)] P’ = [■8(3&3@3&−1)] = P Since P‘ = P P is a symmetric matrix. Let, Q = 𝟏/𝟐 (A − A’) = [■8(0&2@−2&0)] Q’ = [■8(0&−2@2&0)] = – [■8(0&2@−2&0)]= −Q Since Q’ = − Q Q is a skew symmetric matrix. Now, P + Q = 1/2 (A + A’) + 1/2 (A − A’) = A Thus, A is a sum of symmetric & skew symmetric matrix Ex 3.3, 10 Express the following matrices as the sum of a symmetric and a skew symmetric matrix: (ii) [■8(6&−2&2@−2&3&−1@2&−1&3)] Let A = [■8(6&−2&2@−2&3&−1@2&−1&3)] A’ = [■8(6&−2&2@−2&3&−1@2&−1&3)] 1/2 (A + A’) = 1/2 ([■8(6&−2&2@−2&3&−1@2&−1&3)]" + " [■8(6&−2&2@−2&3&−1@2&−1&3)]) = 1/2 [■8(12&−4&4@−4&6&−2@4&−2&6)] = [■8(6&−2&2@−2&3&−1@2&−1&3)] 1/2 (A − A’) = 1/2 ([■8(6&−2&2@−2&3&−1@2&−1&3)]−[■8(6&−2&2@−2&3&−1@2&−1&3)]) = 1/2 [■8(0&0&0@0&0&0@0&0&0)] = [■8(0&0&0@0&0&0@0&0&0)] Let, P = 𝟏/𝟐 (A + A’) = [■8(6&−2&2@−2&3&−1@2&−1&3)] P’ = [■8(6&−2&2@−2&3&−1@2&−1&3)] = P Since P = P’ P is a symmetric matrix. Let, Q = 𝟏/𝟐 (A − A’) = [■8(0&0&0@0&0&0@0&0&0)] Q’ = [■8(0&0&0@0&0&0@0&0&0)] = −[■8(0&0&0@0&0&0@0&0&0)] = –Q Since Q’ = − Q Q is a skew symmetric matrix. Now, P + Q = 1/2 (A + A’) + 1/2 (A − A’) = A Thus, A is a sum of symmetric & skew symmetric matrix Ex 3.3, 10 Express the following matrices as the sum of a symmetric and a skew symmetric matrix: (iii) [■8(3&3&−1@−2&−2&1@−4&−5&2)] Let A = [■8(3&3&−1@−2&−2&1@−4&−5&2)] A’ = [■8(3&−2&−4@3&−2&−5@−1&1&2)] 1/2 (A + A’) = 1/2 ([■8(3&3&−1@−2&−2&1@−4&−5&2)]" + " [■8(3&−2&−4@3&−2&−5@−1&1&2)]) = 1/2 [■8(6&1&−5@1&−4&−4@−5&−4&4)] = [■8(3&1/2&−5/2@1/2&−2&−2@−5/2&−2&2)] 1/2 (A − A’) = 1/2 ([■8(3&3&−1@−2&−2&1@−4&−5&2)]" − " [■8(3&−2&−4@3&−2&−5@−1&1&2)]) = 1/2 [■8(0&5&3@−5&0&6@−3&−6&0)] = [■8(0&−5/2&−3/2@5/2&0&−3@3/2&3&0)] Let, P = 𝟏/𝟐 (A + A’) = [■8(3&1/2&−5/2@1/2&−2&−2@−5/2&−2&2)] P’ = [■8(3&1/2&−5/2@1/2&−2&−2@−5/2&−2&2)] = P Since P’ = P P is a symmetric matrix. Let, Q = 𝟏/𝟐 (A − A’) = [■8(0&5/2&3/2@(−5)/2&0&3@(−3)/2&−3&0)] Q’ = [■8(0&(−5)/2&(−3)/2@5/2&0&−3@3/2&3&0)] = – [■8(0&5/2&3/2@(−5)/2&0&3@(−3)/2&−3&0)] = – Q Since Q’ = − Q Q is a skew symmetric matrix. Let, Q = 𝟏/𝟐 (A − A’) = [■8(0&5/2&3/2@(−5)/2&0&3@(−3)/2&−3&0)] Q’ = [■8(0&(−5)/2&(−3)/2@5/2&0&−3@3/2&3&0)] = – [■8(0&5/2&3/2@(−5)/2&0&3@(−3)/2&−3&0)] = – Q Since Q’ = − Q Q is a skew symmetric matrix. Ex 3.3, 10 Express the following matrices as the sum of a symmetric and a skew symmetric matrix: (iv) [■8(1&5@−1&2)] Let A = [■8(1&5@−1&2)] A’ = [■8(1&−1@5&2)] 1/2 (A + A’) = 1/2 ([■8(1&5@−1&2)]" + " [■8(1&−1@5&2)]) = 1/2 [■8(2&4@4&4)] = [■8(1&2@2&2)] 1/2 (A – A’) = 1/2 ([■8(1&5@−1&2)]−[■8(1&−1@5&2)]) = 1/2 [■8(0&6@−6&0)] = [■8(0&3@−3&0)] Let, P = 𝟏/𝟐 (A + A’) = [■8(1&2@2&2)] P’ = [■8(1&2@2&2)] = P Since P = P’ P is a symmetric matrix. Let, Q = 𝟏/𝟐 (A − A’) = [■8(0&3@−3&0)] Q’ = [■8(0&−3@3&0)] = – [■8(0&3@−3&0)] = −Q Since Q = − Q’ Q is a skew symmetric matrix. Now, P + Q = 1/2 (A + A’) + 1/2 (A − A’) = A Thus, A is a sum of symmetric & skew symmetric matrix
Chapter 3 Class 12 Matrices
Ex 3.1, 9 Important
Example 18 Important
Example 19
Ex 3.2, 7 Important
Ex 3.2, 12 Important
Ex 3.2, 16 Important
Ex 3.2, 17 Important
Ex 3.2, 20 Important
Example 22 Important
Ex 3.3, 4
Ex 3.3, 10 Important You are here
Ex 3.3, 12 Important
Ex 3.4, 15 Important Deleted for CBSE Board 2022 Exams
Ex 3.4, 17 Important Deleted for CBSE Board 2022 Exams
Example 28
Misc. 3 Important
Misc. 9 Important
Misc. 11 Important
Misc. 13 Important
Chapter 3 Class 12 Matrices
About the Author